Contemporary Management of Out-of-hospital Cardiac Arrest in the Cardiac Catheterisation Laboratory: Current Status and Future Directions. Issue 3 (2019) - Pareek, Nilesh; Kordis, Peter; Webb, Ian; Noc, Marko; MacCarthy, Philip; Byrne, Jonathan
No abstract available